Pengaruh Komunikasi Interpersonal Kepala Bidang Dikmenti Terhadap Produktivitas Kerja Pegawai Dinas Pendidikan Provinsi Jawa Barat - Dini Afianti; H. Johar Permana; Diding Nurdin (Jurnal Tata Kelola Pendidikan, 2019)
Research in the wake of the problems how much influence interpersonal communication head Dikmenti field to work productivity of employees at the Education Department of West Java Province. The method used is descriptive method supported by literature study. As well as using the techniques of data collection using the questionnaire enclosed with 4 rating scale (Likert) were distributed to 49 employees especially in the field Dikmenti as samples. The problems of this study (1) how the image of interpersonal communication chief of Dikmenti Education Department of West Java Province, (2) how the employee productivity Education Department of West Java Province, (3) how much influence interpersonal communication head of Dikmenti against employee productivity Education Department of West Java Province. Based on the results of data processing which is calculated by using the technique Weight Means Scores (WMS) shows that the average general tendency for the variable X (Interpersonal Communication) obtained at 3.06 and are in very good category. As for the average general trend in Y (Work Productivity) obtained at 3.45 to be in very good category. The calculation result normality test on the distribution of the data that the variables X and Y have normal distribution. Judging from the calculation of the correlation coefficient (rhitung) using the formula obtained Perason Product Moment correlation coefficient of 0675. Thisshows that there is a strong relationship between the variables X and Y. The test results significantly with t-test obtained t is known ttabel 6.031 and 2.012 compared to 6.03˃ 2012 means that significant relationship between interpersonal communication department heads Dikmenti on productivity employee of West Java Provincial Education Office. To determinethe influence of the variables X and Y is shown from the calculation coefficient of determination (KD) of 43%. This shows that the influence of the head of the field of interpersonal communication Dikmenti against employee productivity Education Department of West Java province by 43% and the remaining 57% is influenced by other factors. Likewise, the results of the regression analysis obtained by the equation Y = 44.949 + 0.525 X means every one-unit change in the variable X will provid a change in the variable Y for 0.525.Berdasarkan the above results it can be concluded that the research hypothesis that there is positive and significant correlation between Interpersonal Communication Division leader Dikmenti the Work Productivity Employee Education Department of West Java Province. The results of this study are expected to provide a benefit both for the institution, employees and for further research that will examine communication problems on the productivity of labor.